Fisheries: satellite surveillance of tuna fishing vessels - Richards, Andrew (Technical Centre for Agricultural and Rural Cooperation, 2005)
Andrew Richards looks at how the people of Tokelau are benefi ting from a wider regional effort to protect their marine resources.